Modificação da celulose de sisal (Agave sisalana) com o poli (álcool vinílico) (PVA) e avaliação de seu potencial no comportamento reológico de óleo pesado - Moreno, Schiliene de Oliveira (2018)
Cellulose is a natural, renewable, non-toxic, biodegradable, more abundant polymer on the planet and can have its structure modified to acquire properties other than pure cellulose. Injection of fluids containing additives for correction of the heavy oil flow profile represents one of several techniques that allow the improvement of the hydrocarbon flow environment in the oil industry, from the reservoir rock to the storage tank. The aim of this study was to modify sisal cellulose (Agave sisalana) from cellulose xanthate with polyvinyl alcohol (PVA) and to evaluate its performance in the viscosity behavior of heavy oil in the form of water emulsion oil (A / O) on laboratory bench. The physico-chemical characterization of sisal cellulose, before and after the modification, was performed by absorption spectroscopy in the infrared region by Fourier Transform (FTIR). As well as, evaluation of the behavior of the intrinsic viscosity (viscosifying potential). The shear apparent viscosity and the viscous flow activation energy were performed by means of rheological measurements. The FTIR spectra confirmed the modification of sisal cellulose by the appearance of the absorption bands at the 1154 cm-1 and 965 cm-1 wave numbers, which evidenced the presence of the -OC(=S)-S group, resulting from the xantation of cellulose, proved by the appearance of a new 880 cm-1 wave number band, which indicated the occurrence of the substitution reaction in the -OH groups of cellulose C-6. The addition of CSM to water evidenced by increasing its apparent viscosity increase, increasing viscosity of CSM with increasing concentration and slight change from Newtonian to non-Newtonian fluid character. The rheological behavior of the heavy oil under study in the presence of CSM was the same as pure heavy oil, ie a nonNewtonian fluid, of the pseudoplastic type, even under saline conditions. The addition of CSM in the oil samples under study, without and with salts, did not significantly change its flow activation energy, remaining in the range of 64.86 to 66.51 kJ / mol, where it was concluded that the CSM has potential of use to guarantee the flow of heavy oil in mature fields.